Pengaruh Faktor Lingkungan Terhadap Pola Distribusi Spasial Dan Temporal Musuh Alami Di Lahan Pertanian - ASYIK NUR ALIFFAH; NUR ALIM NATSIR; MUHAMMAD RIJAL; SALMA SAPUTRI (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Natural enemies are one component of Integrated Pest Management that utilizes non-chemical methods and reduces pesticides. Physical factors of the environment both temperature, humidity and varying light intensity greatly affect the abundance of natural enemies in an agricultural ecosystem. The purpose of this study was to determine the number and types of natural enemies of visitors to the observation plots, species diversity (H ') and the influence of environmental factors on the spatial and temporal distribution patterns of natural enemies on agricultural land. Sampling was conducted in May until July 2019. Observations were made grouped into 4 periods are at 07.00-08.00 WIT, 09.00-10.00 WIT, 12.00-13.00 WIT and at 15.00-16.00 WIT. The observation method used is to use "visual control". The results showed that environmental factors influence the number and type of natural enemies of the plot observation visitors. Natural enemies who visited the observation plot in the agricultural area were 5 families including Coccinellidae, Staphylinidae, Carabidae, Libellulidae, and Formicidae. Shannon - Wienner diversity index of H '>3. Environmental factors affect the presence of natural enemy insects with a correlation of Adjusted R-Square of 0.846 or 84.6%. Key Words: Natural Enemies, Environmental Factors, Spatial, Temporal Distribution